2017
DOI: 10.20998/2074-272x.2017.2.10
|View full text |Cite
|
Sign up to set email alerts
|

Design of the Three-Level Multicriterial Strategy of Hybrid Marine Power Plant Control for a Combined Propulsion Complex

Abstract: Purpose. Efficiency of hybrid ships power plants (SPP) combined propulsion complexes (CPC) by various criteria for energy management systems strategies. Methodology. Based on the classification system topologies SPP CPC for mechanical, electrical and hybrid types of motors schematic diagrams of management strategies for the criterion of minimum power consumption are defined. Changing the technical component of the traditional approach to building hybrid ships electric power systems (SEPS) SPP CPC the principle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 38 publications
0
8
0
2
Order By: Relevance
“…Aboard large specialized vessels, the exhaust gas energy is used in cogeneration plants for the combined production of mechanical and electrical energy. Study [2] considers the appropriate operation principle of vessel thermal machines, whose mechanical energy supplements the energy of the main engine. In a ship's hybrid powerplant, the Stirling engine could be linked to a crankshaft through a hydraulic clutch or work for an electric generator.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Aboard large specialized vessels, the exhaust gas energy is used in cogeneration plants for the combined production of mechanical and electrical energy. Study [2] considers the appropriate operation principle of vessel thermal machines, whose mechanical energy supplements the energy of the main engine. In a ship's hybrid powerplant, the Stirling engine could be linked to a crankshaft through a hydraulic clutch or work for an electric generator.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…However, the patterns of power saving modes are paid very little attention to. Many studies have shown that the propeller screw [5,7] renders main load to the engine of propulsion [2,8] complex with rarely taking into consideration the fact that the load moment M c is close to the "fan" type [11,12]. In the first approximation, a given moment is proportional to the second degree of propeller screw rotation frequency w:…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…where k 1 and k 2 are coefficients that depend on the parameters of propeller (pitch, diameter, etc. ), on the features of design of the propulsion [2,12] complex, navigation mode, level of immersion of the propeller.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…Simulation modeling implies carrying out experiments with the model represented in the form of the set of algorithms describing behavior of CPC SPP. The simulation process is executed by running the multitude of sets of experimental data according to the operating mode and situational factors of the programs based on them [5].…”
Section: Introductionmentioning
confidence: 99%